ТҰЗДАНУ ЖƏНЕ МЫС ИОНДАРЫНЫҢ ƏРТҮРЛІ БИДАЙ СОРТТАРЫНЫҢ ӨСУІНЕ ƏСЕРІ (Experimental biology, 2017)
Separate effect of salinity, copper ions and its combined effect on different varieties of wheat are considered in this article. The following five varieties of wheat (Kazakhstanskaya 3, Shagala, Melturn, Kayr, Kazakhstanskaya ranya) were tested. Biometric measurements of shoоts and roots were made and their biomass was determined. Reduction in the growth of roots and above the ground organs of different varieties of wheat have been noted in a study. The tolerant and sensitive varieties of wheat to effect ofsalinity, cooper and its combines effects were identifyied.
Keywords: salinity; copper ions